PENINGKATAN MOTIVASI DAN KEAKTIFAN BELAJAR IPAS MELALUI MEDIA EVALUASI INTERAKTIF KAHOOT PADA SISWA KELAS V SDS AL-WASHLIYAH 01 MEDAN - Rizkiyani, Dinda; Juwita, Putri; Banjarnahor, Desma; Rinanda, Amalia; Rinanda, Aisyah; Nurfazri, Juliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The success of natural science learning (IPAS) in elementary schools cannot be separated from students' learning motivation and activity during the learning process. In practice, learning evaluations that still rely on traditional methods often fail to optimally encourage student engagement. This condition indicates the need for alternative evaluations that are more interactive and relevant to the characteristics of elementary school students. This study focused on the use of Kahoot as a game-based evaluation media to improve learning motivation and activity of fifth-grade students at SDS Al-Washliyah 01 Medan. The approach used was Classroom Action Research (CAR) with two action cycles. Each cycle was carried out through the stages of planning, action implementation, observation, and reflection to continuously evaluate the effectiveness of the actions taken. The research subjects consisted of 23 students. Data were collected using a learning motivation questionnaire, student activity observation sheets, and documentation of the learning process. Data analysis was carried out quantitatively in a descriptive manner by comparing the percentage achievements at the pre-cycle stage, cycle I, and cycle II. The results of the study showed a significant increase in both variables being examined. Students' learning motivation, which initially was at 62%, rose to 78% in cycle I and increased further to 89% in cycle II. Meanwhile, student activeness also showed a positive trend, increasing from 58% in the pre-cycle to 73% in cycle I, and reaching 91% in cycle II. These findings indicate that the use of Kahoot as an evaluation tool is able to encourage more active student participation and create a more engaging, student-centered IPAS learning environment.